THE USE OF NUMBER BAG MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES ABOUT ADDITION MATERIALS IN CLASS I SD INPRES SALUMONI - Ni Made Yuliani; I Ketut Kertayasa; Ni Putu Satya Narayanti (STAH Dharma Sentana Sulawesi Tengah, 2023)
This study aims to find out the results of learning addition material using number bag media and find out student responses in using number bag media for addition material in class I SD Inpres Salumoni. Classroom Action Research (PTK) is used as a research design consisting of planning, implementation, observation and reflection. The instruments in this research consist of observations, documentation, interview techniques and test administration. Data analysis in this study consisted of two methods, namely quantitative data analysis and qualitative data analysis. By using number bag media, student learning outcomes increase. This is as seen in the results of the post test cycle I and cycle II. In cycle I, the percentage of classical mastery was 67.82% and classical learning mastery was 56.52%. Whereas in cycle II the percentage of classical mastery was 86.08% and classical learning mastery was 91.30%. So it can be concluded that the use of number bag media can improve student learning outcomes.